Psychometric Properties of the MSLQ-B for Adult Distance Education in China - Zhou, Ying; Wang, Jianhua (Frontiers in Psychology, 2021)
In the education context, The Motivational Strategies for Learning Questionnaire (MSLQ) is extensively used in assessing self-regulated learning strategies. However, more research is needed to address whether it is applicable for distance education. The exploratory and confirmatory factor analysis were used to test the Chinese version of the Motivated Strategies for Learning Questionnaire part-B for distance learning (MSLQ-B-DL) using two samples totalling 385 participants. This paper substantiates MSLQ-B-DL’s criterion-related, convergent, and factorial validity, as well as its internal consistency, in China. Specifically, the concurrent validity of the MSLQ-B-DL was shown from three aspects: (a) the negative correlation of MSLQ-B-DL with trait procrastination; (b) the positive correlation of MSLQ-B-DL with self-control; and (c) the positive correlation of MSLQ-B-DL with instrumental help-seeking and the former’s negative correlation with help-seeking avoidance and executive help-seeking. Finally, this study highlights the MSLQ-B-DL’s validity and reliability in evaluating the learning strategies in adult distance education in China.